Parasite-Derived Excretory-Secretory Products Alleviate Gut Microbiota Dysbiosis and Improve Cognitive Impairment Induced by a High-Fat Diet - Wu, Jiacheng; Zhu, Yuqi; Zhou, Limian; Lu, Yang; Feng, Tingting; Dai, Mengyu; Liu, Jiaxue; Xu, Wen; Cheng, Wanpeng; Sun, Fenfen; Liu, Hua; Pan, Wei; et al. (Frontiers in Immunology, 2021)
High-fat (HF) diet-induced neuroinflammation and cognitive decline in humans and animals have been associated with microbiota dysbiosis via the gut-brain axis. Our previous studies revealed that excretory-secretory products (ESPs) derived from the larval Echinococcus granulosus (E. granulosus) function as immunomodulators to reduce the inflammatory response, while the parasitic infection alleviates metabolic disorders in the host. However, whether ESPs can improve cognitive impairment under obese conditions remain unknown. This study aimed to investigate the effects of E. granulosus-derived ESPs on cognitive function and the microbiota-gut-brain axis in obese mice. We demonstrated that ESPs supplementation prevented HF diet-induced cognitive impairment, which was assessed behaviorally by nest building, object location, novel object recognition, temporal order memory, and Y-maze memory tests. In the hippocampus and prefrontal cortex, ESPs suppressed neuroinflammation and HF diet-induced activation of the microglia and astrocytes. Moreover, ESPs supplementation improved the synaptic ultrastructural impairments and increased both pre- and postsynaptic protein levels in the HIP and PFC compared to the HF diet-treated group. In the colon, ESPs reversed the HF diet-induced gut barrier dysfunction, increased the thickness of colonic mucus, upregulated the expression of zonula occludens-1 (ZO-1), attenuated the translocation of bacterial endotoxins, and decreased the colon inflammation. Notably, ESPs supplementation alleviated the HF diet-induced microbiota dysbiosis. After clarifying the role of antibiotics in obese mice, we found that broad-spectrum antibiotic intervention abrogated the effect of ESPs on improving the gut microbiota dysbiosis and cognitive decline. Overall, the present study revealed for the first time that the parasite-derived ESPs alleviate gut microbiota dysbiosis and improve cognitive impairment induced by a high-fat diet. This finding suggests that parasite-derived molecules may be used to explore novel drug candidates against obesity-associated neurodegenerative diseases.